2014
DOI: 10.5694/mja13.11052
|View full text |Cite
|
Sign up to set email alerts
|

Dementia prevalence and incidence among the Indigenous and non‐Indigenous populations of the Northern Territory

Abstract: The NT Indigenous population has a much higher prevalence and incidence of dementia and younger onset of disease compared with their non-Indigenous counterparts. The results highlight the urgent need for interventions to moderate the emerging impact of dementia in the Australian Indigenous population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 11 publications
4
79
0
4
Order By: Relevance
“…Recent studies in the Kimberley [4], New South Wales [5] and the Northern Territory [6] have demonstrated that dementia occurs at up to five times the rate of the general population. The rates within the Aboriginal population are slightly higher in remote compared with regional and urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in the Kimberley [4], New South Wales [5] and the Northern Territory [6] have demonstrated that dementia occurs at up to five times the rate of the general population. The rates within the Aboriginal population are slightly higher in remote compared with regional and urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Art centres are acknowledged as central to the social, cultural and economic well-being of many artists and communities [13]. Artists aged over 55 years are estimated to comprise around 30% of the remote artist population [13], while the number with dementia is unknown; the evidence suggests the numbers are likely to be significant [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies are repeatedly reporting much higher rates of dementia in Aboriginal Australians, compared with nonIndigenous Australians, with rates amongst the highest in the world [16][17][18]. A longitudinal study of indigenous people living in rural and remote areas of the Kimberley, Western Australia had a dementia prevalence of 14.8% [16] and a study of indigenous people living in urban and regional New South Wales found a prevalence of 13.4%, agestandardised to 21%, compared with the overall Australian prevalence of 6.8% [17].…”
Section: Epidemiological Studies In Oceaniamentioning
confidence: 99%
“…Mais da metade dos estudos relataram o início precoce de comprometimento cognitivo (demência ou comprometimento cognitivo), ou seja, antes dos 65 anos de idade (Jervis et al, 2007;British, 2007;Smith et al, 2008;Jacklin et al, 2012, Brucki, Nitrini, 2014Lo Giudice, 2015). A taxa de incidência de indígenas para não indígena foi maior nos grupos etários mais jovens (45 e 64 anos) (Li et al, 2014). Um estudo mostrou um efeito do sexo sobre o desempenho cognitivo (Jervis et al, 2007).…”
Section: (Tabela 2)unclassified
“…Além disso, as populações indígenas em grupos etários mais jovens, entre 45 e 64 anos, mostraram as taxas de incidência mais elevadas em comparação com as populações não indígenas com a mesma idade (Li et al, 2014). A percentagem de pessoas indígenas com pouca educação formal ou nenhuma foi altamente significativa e nenhuma educação formal entre australianos aborígenes foi associada com demência (Smith et al, 2010).…”
Section: (Tabela 2)unclassified